Evaluation of the soil water regime in the microregion of Vitória de Santo Antão–Pernambuco - Ribeiro, Eberson Pessoa; Souza, Carolayne Silva (Revista Geama, 2018)
<span style="letter-spacing: -0.2pt; font-family: 'Century',serif; font-size: 9pt; mso-bidi-font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The knowledge of the amount of water in the soil is essential for the development of effective agricultural planning. Therefore, the objective of the present work was to determine the soil water regime for the microregion of Vitória de Santo. It was used in this study the mean monthly rainfall values of the historical series from 1950 to 2015, measured from 5 meteorological stations. Since obtaining the average monthly air temperature data was employed Estima_T software, which estimates air temperatures through multiple regressions depending on local coordinates: longitude, latitude and altitude. The spatial representation of the main parameters of this study was performed by applying the kriging. The BHC extract revealed that the dry and rainy seasonality of the microregion affects the levels of ETR, DEF and EXC. The ETR presented approximately 916 mm / year, decreasing gradually from northeast to southwest portion due to increased altitude. DEF has obtained a total of 336 mm / year, concentrating on the period from October to March, where the water scarcity is mainly located in the center-west portion. The EXC had a total of 248 mm / year, being restricted to the months of May, June and July, in which the extreme portions of the northeast and south-west of the microregion are the ones with the highest rates, above 360 mm / year. The evaluation of the soil water regime for the Vitória de Santo Antão microregion allowed to know the water demand of the soil in different periods of the year.